1995
DOI: 10.2307/1131188
|View full text |Cite
|
Sign up to set email alerts
|

Affective Influences on Startle in Five-Month-Old Infants: Reactions to Facial Expressions of Emotion

Abstract: Convergent methodologies from studies of fear-potentiated startle in animals and studies of affective modulation of reflex blinks in humans were adapted in order to investigate infants' sensitivity to affective information conveyed by facial expressions of emotion. While 5-month-old infants viewed photographic slides of faces posed in happy, neutral, or angry expressions, a brief acoustic noise burst was presented to elicit the blink component of human startle. Blink size was augmented during the viewing of an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
51
1
1

Year Published

1997
1997
2014
2014

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(58 citation statements)
references
References 0 publications
5
51
1
1
Order By: Relevance
“…There is one study demonstrating that the affective modulation of the startle reflex to angry and happy expressions can be found in 5 month old infants (Balaban, 1995), while a recent study did not find affect modulated startle responses to neutral and angry facial expressions in four to eight year old children (Waters et al, 2008). In adults, one study with pictures of negative infant emotional faces (crying babies) did not find the expected startle modulation (Spangler et al, 2001).…”
Section: Emotional Facial Expressionsmentioning
confidence: 96%
“…There is one study demonstrating that the affective modulation of the startle reflex to angry and happy expressions can be found in 5 month old infants (Balaban, 1995), while a recent study did not find affect modulated startle responses to neutral and angry facial expressions in four to eight year old children (Waters et al, 2008). In adults, one study with pictures of negative infant emotional faces (crying babies) did not find the expected startle modulation (Spangler et al, 2001).…”
Section: Emotional Facial Expressionsmentioning
confidence: 96%
“…Concurring with these observations, many contemporary theories of conversion disorder conceptualize conversion symptoms as part of the individuals' emotional response to threat, reflecting either (a) the implicit processing of information resulting in an automatic motorsensory response or (b) errors related to how information about body state is processed or represented within the brain [1]. A variety of methodologies-each focusing on a different level of the mind-body system-have been used to analyze human emotional responses to threat [2][3][4][5][6][7][8][9]. One recently developed method for assessing self-protective emotional responses derives from the dynamic-maturational theory of attachment (DMM), a theory about human emotional development across the lifespan [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, limb weakness refers to motor paresis, where the child has significantly less than full capacity to move the limb, with the amount of impairment varying from child to child (and over time, for each child). We make this distinction because limb paralysis, unlike limb weakness, is difficult to enact over time 2. A number of authors suggest that strong negative emotions may cause inhibition of micturition via sympathetic activation, which causes active contraction of internal and external sphincter muscles of the bladder sphincter.…”
mentioning
confidence: 99%
“…Numerous studies have revealed modulatory effects of affectively positive or negative foreground stimuli on the startle blink reflex, especially at later probe times (e.g., Balaban, 1995;Bradley et al, 1999;Cook et al, 1992;Lang, 1995;Stritzke et al, 1995). Specifically, in relation to startle reactivity during a neutral picture foreground, the startle blink response is inhibited during viewing of pleasurable picture stimuli and potentiated during viewing of aversive picture stimuli.…”
mentioning
confidence: 99%